2009
DOI: 10.1007/s10661-009-1075-6
|View full text |Cite
|
Sign up to set email alerts
|

Silica glass modified with flavonoid derivatives for preconcentration of some toxic metal ions in water samples and their determination with ICP-MS

Abstract: Quercetin (3,3',4',5,7-pentahydroxyflavone) chemically bonded through pyran rearrangement on modified controlled pore silica glass (QCPSG) with a capacity 0.213 mmol/g was used for solid phase extraction of some toxic metal and metalloid ions. The newly designed QCPSG quantitatively sorbs As(V), Cd(II), Hg(II), and Pb(II) at the pH range 7.5-8.5 after 10 min of stirring. HCl (1 mol L(-1)) instantaneously elutes all the metal ions. The sorption capacity of the ion collector is 0.42, 0.46, 0.53, and 0.49 mmol g(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 21 publications
1
4
0
Order By: Relevance
“…This may be attributed to the domestic and anthropogenic activities in these regions which are also shown in the water quality and nutrients measurements. It can be also concluded that the concentrations of heavy metal ions are within the permissible levels and are in agreement with those reported previously [39][40][41].…”
Section: Analysis Of Real Water Samplessupporting
confidence: 91%
See 1 more Smart Citation
“…This may be attributed to the domestic and anthropogenic activities in these regions which are also shown in the water quality and nutrients measurements. It can be also concluded that the concentrations of heavy metal ions are within the permissible levels and are in agreement with those reported previously [39][40][41].…”
Section: Analysis Of Real Water Samplessupporting
confidence: 91%
“…Surface water samples were collected from Nile River at Mansoura, Miet Antar, Sherbin, and Faraskour; brackish water at Damietta bridge, Elgerbi, Ezbet Elborg and Elmanzalah lake and Mediterranean Sea at Port Fouad and Port Said. Table 8 shows the results of the application process in comparison with the standard methods: direct HGAAS in the case of Hg(II) and solvent extraction (ammonium pyrrolidinedithiocarbamate in methyl isobutyl ketone) followed by ICP-MS determination in the case of the other metal ions [39]. It can be concluded that the concentration of the investigated metal ions increases obviously in the region beginning from Damietta Bridge to the River effluent and in Elmanzalah Lake.…”
Section: Analysis Of Real Water Samplesmentioning
confidence: 99%
“…The same batch of samples was also analysed by ICP-MS aer solvent extraction with APDC/MIBK. 29 The paired t-test was applied to the results obtained by the proposed and the reference methods, and it showed that the calculated t values were lower than the tabulated t value (t ¼ 2.36, n ¼ 5, P ¼ 0.05). This suggested that at the 95% condence level, the difference between the results obtained by the two methods were statistically not signicant.…”
Section: Applicationsmentioning
confidence: 96%
“…Neutron activation analysis , inductively coupled plasma (ICP) mass spectrometry , ICP atomic emission spectrometry , electrothermal atomic absorption spectrometry , and flame atomic absorption spectrometry (FAAS) are the main instrumental techniques determining trace elements in various samples. FAAS has been widely used for the determination of trace amounts of metal ions.…”
Section: Introductionmentioning
confidence: 99%